2007
DOI: 10.1126/science.1153006
|View full text |Cite
|
Sign up to set email alerts
|

Are There Alfvén Waves in the Solar Atmosphere?

Abstract: The Sun's outer coronal layer exists at a temperature of millions of kelvins, much hotter than the solar surface we observe. How this high temperature is maintained and what energy sources are involved continue to puzzle and fascinate solar researchers. Recently, the Hinode spacecraft was launched to observe and measure the plasma properties of the Sun's outer layers. The data collected by Hinode reveal much about the role of magnetic field interactions and how plasma waves might transport energy to the corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
129
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(131 citation statements)
references
References 13 publications
2
129
0
Order By: Relevance
“…Non-thermal line narrowing / broadening due to Alfvén waves has been reported by Harrison et al (2002) / Erdélyi et al (1998), Banerjee et al (1998) and O'Shea et al (2003). Alfvén waves have possibly been observed in the corona (Okamoto et al 2007;Tomczyk et al 2007) and chromosphere (De Pontieu et al 2007;Jess et al 2009), although these claims are subject to intense discussion (Erdélyi & Fedun 2007;Van Doorsselaere et al 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Non-thermal line narrowing / broadening due to Alfvén waves has been reported by Harrison et al (2002) / Erdélyi et al (1998), Banerjee et al (1998) and O'Shea et al (2003). Alfvén waves have possibly been observed in the corona (Okamoto et al 2007;Tomczyk et al 2007) and chromosphere (De Pontieu et al 2007;Jess et al 2009), although these claims are subject to intense discussion (Erdélyi & Fedun 2007;Van Doorsselaere et al 2008).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, propagating transverse waves in thin threads of solar prominences have been observed (e.g., Lin et al 2007Lin et al , 2009) and Alfvénic waves in bright points have been reported (Jess et al 2009). The role and implications of the observed Alfvénic waves for the heating of the solar atmosphere have been discussed by, e.g., Erdélyi & Fedun (2007); De Pontieu et al (2007); McIntosh et al (2011);Cargill & De Moortel (2011).…”
Section: Introductionmentioning
confidence: 99%
“…Based on MHD wave theory, a number of works have interpreted the observed waves as propagating kink MHD waves (e.g., Erdélyi & Fedun 2007;Van Doorsselaere et al 2008;Lin et al 2009;Pascoe et al 2010Pascoe et al , 2011Terradas et al 2010;Verth et al 2010Verth et al , 2011Soler et al 2011a,b,c). Kink waves are transverse waves with mixed fast MHD and Alfvénic properties (see, e.g., Edwin & Roberts 1983;Goossens et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Sakurai et al 1991;Goossens et al , 2011Ballai & Erdélyi 2002). Wave propagation in twisted magnetic tubes has been investigated by Bogdan (1984), Bennett et al (1999), Erdélyi & Carter (2006), Carter & Erdélyi (2007, Erdélyi & Fedun (2007), and Terradas & Goossens (2012).…”
Section: Introductionmentioning
confidence: 99%